2006
DOI: 10.1002/pmic.200500312
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of quorum sensing in Rhizobium leguminosarum biovar viciae UPM791

Abstract: Production of quorum-sensing signal molecules of the acyl-homoserine lactone (AHL) type by Rhizobium leguminosarum bv. viciae UPM791 is dependent on its plasmid content. Curing of two of its four native plasmids, pUPM791d and pSym, resulted in loss of production of the largest (C(14)) and the three smaller (C(6)-C(8)) AHLs, respectively. Introduction of a lactonase-containing plasmid resulted in AHL signal degradation and quorum quenching. The quorum-dependent proteome was studied in these strains by DIGE. Quo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In Gram-negative bacteria, the main characterized QS system involves three key molecular elements ( Venturi and Subramoni, 2009 ): (i) N-acyl homoserine lactones (AHLs), which act as autoinducers (AIs); (ii) the AHLs synthase encoded by a luxI -like gene; (iii) a transcriptional regulator, which is encoded by a luxR -like gene and which binds AHL molecules and modulates the expression of different target genes that constitute the QS regulon. Depending on the bacterial species and also on the experimental strategies (transcriptomic or proteomic), the size of the QS regulons oscillates between 3 and 8% of the identified ORFs ( Vasil, 2003 ; Wagner et al, 2003 ; Cantero et al, 2006 ; Qin et al, 2007 ; Stevens et al, 2011 ; Majerczyk et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Gram-negative bacteria, the main characterized QS system involves three key molecular elements ( Venturi and Subramoni, 2009 ): (i) N-acyl homoserine lactones (AHLs), which act as autoinducers (AIs); (ii) the AHLs synthase encoded by a luxI -like gene; (iii) a transcriptional regulator, which is encoded by a luxR -like gene and which binds AHL molecules and modulates the expression of different target genes that constitute the QS regulon. Depending on the bacterial species and also on the experimental strategies (transcriptomic or proteomic), the size of the QS regulons oscillates between 3 and 8% of the identified ORFs ( Vasil, 2003 ; Wagner et al, 2003 ; Cantero et al, 2006 ; Qin et al, 2007 ; Stevens et al, 2011 ; Majerczyk et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…These global omics approaches revealed that QS can affect several percent of the protein or gene content in bacteria, as observed for B. phymatum or Rhizobium leguminosarum (Coutinho et al 2013 ;Cantero et al 2006 ).…”
Section: Omics Approaches To Identify Qs-regulated Genesmentioning
confidence: 97%
“…Recently, Cantero et al 42 performed a comparative proteome analysis to identify QS‐regulated proteins of R. leguminosarum bv. viciae UMP791, a typical pea‐nodulating strain harboring four plasmids coding for different AHL synthases and genes involved in symbiotic functions.…”
Section: Qs‐regulated Proteins Assessed By Proteomicsmentioning
confidence: 99%